miR-194 Inhibits Innate Antiviral Immunity by Targeting FGF2 in Influenza H1N1 Virus Infection - Wang, Keyu; Lai, Chengcai; Gu, Hongjing; Zhao, Lingna; Xia, Min; Yang, Penghui; Wang, Xiliang (Frontiers in Microbiology, 2017)
Fibroblast growth factor 2 (FGF2 or basic FGF) regulates a wide range of cell biological functions including proliferation, angiogenesis, migration, differentiation, and injury repair. However, the roles of FGF2 and the underlying mechanisms of action in influenza A virus (IAV)-induced lung injury remain largely unexplored. In this study, we report that microRNA-194-5p (miR-194) expression is significantly decreased in A549 alveolar epithelial cells (AECs) following infection with IAV/Beijing/501/2009 (BJ501). We found that miR-194 can directly target FGF2, a novel antiviral regulator, to suppress FGF2 expression at the mRNA and protein levels. Overexpression of miR-194 facilitated IAV replication by negatively regulating type I interferon (IFN) production, whereas reintroduction of FGF2 abrogated the miR-194-induced effects on IAV replication. Conversely, inhibition of miR-194 alleviated IAV-induced lung injury by promoting type I IFN antiviral activities in vivo. Importantly, FGF2 activated the retinoic acid-inducible gene I signaling pathway, whereas miR-194 suppressed the phosphorylation of tank binding kinase 1 and IFN regulatory factor 3. Our findings suggest that the miR-194-FGF2 axis plays a vital role in IAV-induced lung injury, and miR-194 antagonism might be a potential therapeutic target during IAV infection.